Perceptual effects in relativity and astrophysics - THULASIDAS, Manoj (Institutional Knowledge at Singapore Management University, 2009)
Cognitive neuroscience treats space and time as our brain's representation of our sensory inputs. In this view, our perceptual reality is only a distant and convenient mapping of the physical processes causing the sensory inputs. Sound is a mapping of auditory inputs, and space is a representation of visual inputs. Any limitation in the chain of sensing has a specific manifestation on the cognitive representation that is our reality. One physical limitation of our visual sensing is the finite speed of light, which manifests itself as a basic property of our space time. In this article, we look at the consequences of the limited speed of our perception, namely, the speed of light, and show that they are remarkably similar to the coordinate transformation in special relativity. From this observation, and inspired by the notion that space is merely a cognitive model created out of light inputs, we examine the implications of treating the special theory of relativity as a formalism for describing the perceptual effects due to the finite speed of light. Using this framework, we show that we can unify and explain a wide array of seemingly unrelated astrophysical and cosmological phenomena. When we identify the manifestations of the limitations in our perception and cognitive representation, we can understand the consequent constraints on our space and time, leading to a new understanding of astrophysics and cosmology. (C) 2009 Physics Essays Publication. [DOI: 10.4006/1.3230499]